2021
DOI: 10.1177/11206721211001716
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease assessment in patients with neovascular age-related macular degeneration in Spain: Results of the AMD-MANAGE study

Abstract: Background/Aims: The present study evaluates the burden of neovascular age-related macular degeneration (nAMD) to Healthcare System and patients, describing the management and treatment effectiveness in routine clinical practice in Spain. Methods: Observational, non-interventional, cross-sectional, retrospective (24 months), multicentre study including patients who started treatment with licensed vascular endothelial growth factor inhibitors (anti-VEGF) for nAMD with a minimum follow up of 24 months. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“… Another analysis of anti-VEGF regimens in patients with nAMD reported a preference for treat-and-extend (46%), followed by pro re nata (44%), and fixed (4%) anti-VEGF regimens, thereby reducing the burden for patients and caregivers and use of health care resources. These studies highlight the unmet need for improvements in the treatment approach for patients with nAMD. In addition, these findings suggest that patients may prefer less burdensome treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Another analysis of anti-VEGF regimens in patients with nAMD reported a preference for treat-and-extend (46%), followed by pro re nata (44%), and fixed (4%) anti-VEGF regimens, thereby reducing the burden for patients and caregivers and use of health care resources. These studies highlight the unmet need for improvements in the treatment approach for patients with nAMD. In addition, these findings suggest that patients may prefer less burdensome treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…One study comparing pro re nata vs monthly injections with ranibizumab in patients with nAMD reported that a higher proportion of patients favored a less burdensome pro re nata regimen over monthly injections (53% vs 38%, respectively) . Another analysis of anti-VEGF regimens in patients with nAMD reported a preference for treat-and-extend (46%), followed by pro re nata (44%), and fixed (4%) anti-VEGF regimens, thereby reducing the burden for patients and caregivers and use of health care resources . These studies highlight the unmet need for improvements in the treatment approach for patients with nAMD.…”
Section: Discussionmentioning
confidence: 99%
“…The principal burden associated with anti-VEGF therapy is the need for frequent treatment and monitoring, which represents considerable loss of patient and caregiver time and leads to reduced work productivity, activity impairment, and increased indirect costs. [15][16][17][18] Patient anxiety related to their intravitreal injection was also found to be an important burden in a European study, with 93% of 131 patients reporting anxiety, including 54% for ≥2 days prior to their appointment. 17 Patient-reported effects of this anxiety included inability to relax (58%), disrupted sleep (26%), reduced concentration (13%), and headache and/or nausea (10%).…”
Section: Introductionmentioning
confidence: 99%
“…Patients over the age of 50 years with nAMD receiving anti-VEGF drugs for at least 2 years and retina specialists working in the Spanish National Healthcare System (SNHS) were invited to participate in the study. They were selected from the universe of the AMD-MANAGE study (patients recruited from 20 public and private tertiary hospitals from different Spanish regions that met the following selection criteria: adult naïve (no previous exposure to anti-VEGF treatment) patients �50 years with confirmed nAMD diagnosis who started anti-VEGF treatment between November 1st, 2016 and February 28th, 2017, with a follow-up of 24 months and not participating in any other clinical study) (S1 Table) [22].…”
Section: Study Participantsmentioning
confidence: 99%
“…results [16-20, 30, 31]. Data from real world evidence on treatment burden shows that at 2 years approximately 70% of visit intervals (n = 1.344) were � 8 weeks (<4 weeks: 20%; 4-6 weeks: 30%; 6-8 weeks: 14%) while nearly 50% of injection intervals (n = 781) were � 8 weeks (<4 weeks: 4% 4-6 weeks: 26%, 6-8 weeks: 18%) [22]. The burden of treatment related to the need for frequent visits to the hospital may not only have an impact on patients and retinal specialists, but also on caregivers [33].…”
Section: Plos Onementioning
confidence: 99%